Analysis of the Use of Digital Payments at Foresthree Coffee Transyogi - Resya Alfianty; Osly Usman; Suherdi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The aim of this research is to find out how digital payments are used at Foresthree Coffee Transyogi, to find out the obstacles to using digital payments at Foresthree Coffee Transyogi, and also to find out solutions to overcome the obstacles faced when making transactions using digital payments at Foresthree Coffee Transyogi. This research uses a qualitative method with a descriptive approach that focuses on observing phenomena or events in the original conditions obtained. In collecting data sources, researchers collect data in the form of primary data and secondary data. Data collection in this research was collected directly from the original source using data collection techniques with interviews, observation and documentation. Based on the results of this research, it can be seen that the use of digital payments at Foresthree Coffee Transyogi makes it quite easy for baristas and consumers to carry out transactions. However, using digital payments is not yet an option, this can be seen from consumers’ choices when making transactions. There are problems in the form of problems with the system and an unstable internet connection that makes it dependent on the internet. Based on these obstacles, there are several suggestions, namely carrying out routine maintenance to prevent technical problems, checking the device before use to minimize the occurrence of problems, carrying out regular evaluations to identify and fix problems, and providing a stable internet connection to ensure smooth transactions.